The travel of a reform idea participatory budgeting and its adaptation in the Philippines - Ilago, Simeon A. (2016)
The article looks at a particular experience of the Philippine government in participatory budgeting through the bottom-up budgeting (BUB) program adopted by the Aquino administration. It frames the implementation of the BUB program within the historical development and context of budgeting reform. The program is discussed in terms of how participatory budgeting is defined, its process, and decision making. By situating BUB in the context of Philippine budgeting reform history, it has shown how its adoption and adaptation signified a reform attempt quite distinct from the more technocratic attempts on public financial management reform. By locating it within the historical evolution of participatory budgeting worldwide, it presented the constraints of the current BUB model and why it should not be expected to generate a radical transformation of the current decisionmaking system at the local government level, contrary to normative expectations.
Keywords: Budget management; Budget reform; Bottom-Up Budgeting (BUB); Public finance -- Government policy; Local Poverty Reduction Action Planning (LPRAP)